The Effective School Strategic Plan Implementation: A Best Practice of School Improvement - Nugraha, Dera; Reftyawati, Dian; Sari, Yeasy Agustina (CV. Creative Tugu Pena, 2020)
Schools face the social changes quickly that was caused by the global village phenomenon. It makes schools’ strategic plans and their implementation strategies becoming important topics to be discussed. This study aimed to know how the implementation of State of Junior High School (SMP) Islam Cendekia Cianjur strategic plan during academic year 2018/2019. A school in West Java addresses religious and globally competed graduation. The research used qualitative-descriptive. Collecting data used observation, interview, and document analysis instruments. The finding showed that SMP Islam Cendekia Cianjur achieved maximum result in implementing annual work plan. Almost all program objectives were realized, some even exceeded the annual targets set due to their well-organized of strategic plan and the accuracy of its implementation strategy. The collaboration of principal’s managerial and social competencies and participative leadership approach have proven effectively in embodying school annual work plan. The principal succeed in improving educators’ competencies and their working performances, as well as in collaboration with various potential parties. The challenges were related to school human resources. Keywords: Effective School. Strategic Plan Implementation